Comparison of predicted psychological distress among workers between artificial intelligence and psychiatrists: a cross-sectional study in Tsukuba Science City, Japan. Issue 6 (23rd June 2021) - Doki, Shotaro; Sasahara, Shinichiro; Hori, Daisuke; Oi, Yuichi; Takahashi, Tsukasa; Shiraki, Nagisa; Ikeda, Yu; Ikeda, Tomohiko; Arai, Yo; Muroi, Kei; Matsuzaki, Ichiyo
Abstract : Objectives: Psychological distress is a worldwide problem and a serious problem that needs to be addressed in the field of occupational health. This study aimed to use artificial intelligence (AI) to predict psychological distress among workers using sociodemographic, lifestyle and sleep factors, not subjective information such as mood and emotion, and to examine the performance of the AI models through a comparison with psychiatrists. Design: Cross-sectional study. Setting: We conducted a survey on psychological distress and living conditions among workers. An AI model for predicting psychological distress was created and then the results were compared in terms of accuracy with predictions made by psychiatrists. Participants: An AI model of the neural network and six psychiatrists. Primary outcome: The accuracies of the AI model and psychiatrists for predicting psychological distress. Methods: In total, data from 7251 workers were analysed to predict moderate and severe psychological distress. An AI model of the neural network was created and accuracy, sensitivity and specificity were calculated. Six psychiatrists used the same data as the AI model to predict psychological distress and conduct a comparison with the AI model. Results: The accuracies of the AI model and psychiatrists for predicting moderate psychological distress were 65.2% and 64.4%, respectively, showing no significant difference. The accuracies of the AI model and psychiatrists for predicting severe psychological distress were 89.9% and 85.5%, respectively, indicating that the AI model had significantly higher accuracy. Conclusions: A machine learning model was successfully developed to screen workers with depressed mood. The explanatory variables used for the predictions did not directly ask about mood. Therefore, this newly developed model appears to be able to predict psychological distress among workers easily, regardless of their subjective views.